PRELIMINARY INVESTIGATION OF GENDER MICROAGGRESSION EXPERIENCES IN STUDENTS WITH VEILED : IMPLICATIONS FOR COUNSELING SERVICES IN HIGHER EDUCATION - Irawan, Andi Wahyu; Sari, Elly Kartika; Pimada, Luluk Humairo; Dwisona, Dwisona; Pratiwi, Yasintha Sari (Jurnal Bimbingan dan Konseling Borneo, 2023)
AbstrakThis article focuses on the experience of gender microaggression in students with veiled in Indonesia. Qualitative methods with Interpretative Phenomenological Analysis are used to determine how Students with veiled interpret the understanding of gender microaggression. The findings revealed that they often experienced subtle and inconspicuous discrimination. This fact is known as gender microaggression. The narrative suggests that participants experienced gender microaggression due to their appearance. The perpetrator considered that the participants were religious fanatical and incompetent. Participants also had to face social isolation and were marginalized within their groups. In addition, participants can feel the positive impact of avoiding sexual objectification. In light of these findings, it is recommended that counseling services in higher education institutions take proactive steps to prevent and address gender microaggressions. Additionally, counselors need to have competence in providing inclusive services.Keywords : Gender, Microaggression, Veiled, Preliminary Investigation, Students.          AbstrakArtikel ini berfokus pada pengalaman mikroagresi gender pada pelajar berkerudung di Indonesia. Metode kualitatif dengan Analisis Fenomenologi Interpretatif digunakan untuk mengetahui bagaimana Siswa berjilbab memaknai pengertian mikroagresi gender. Temuannya mengungkapkan bahwa mereka sering mengalami diskriminasi yang tidak kentara dan tidak mencolok. Fakta ini dikenal sebagai agresi mikro gender. Narasinya menunjukkan bahwa peserta mengalami mikroagresi gender karena penampilan mereka. Pelaku menilai pesertanya fanatik terhadap agama dan tidak kompeten. Peserta juga harus menghadapi isolasi sosial dan terpinggirkan dalam kelompoknya. Selain itu, peserta juga bisa merasakan dampak positif dari menghindari objektifikasi seksual. Berdasarkan temuan ini, direkomendasikan agar layanan konseling di institusi pendidikan tinggi mengambil langkah proaktif untuk mencegah dan mengatasi agresi mikro gender. Selain itu, konselor juga perlu memiliki kompetensi dalam memberikan layanan inklusif.Kata Kunci : Gender, Mikroagresi, Bercadar, Investigasi Pendahuluan, Siswa.